Relationship between Active Physical Exercise And Sleep Quality With Physical Fatigue in Elderly - Ramdhany Ismahmudi; Alfi Ari Fakhrurizal (University of Muhammadiyah Semarang, 2020)
Physical exercise is any form of activity carried out by an individual, especially the elderly, to improve physical fitness and physical conditions, with the main objective being to increase strength, cardiorespiratory endurance, speed, skills,, and flexibility. In the elderly, physical training aims to improve the quality of life, so they can get through their old days in a fit. The purpose of this study is to find out how the relationship between active physical activity and sleep quality with physical fatigue that occurs in the elderly in the working area. This research is a descriptive qualitative study using a cross-sectional study approach. Sampling is done by the method of Total Sampling, where all respondents will be involved in research activities, with a total sample of 125 respondents. The research activity was carried out for approximately 1 month starting from July 23-August 24, 2019 at the Harapan Baru Health Center in Samarinda. The result of this research showed the significant relationship between physical activity with fatigue.